Evaluating the Effectiveness of Electronic Information Resource Organisation Strategies in Academic Libraries in South Africa - Jiyane, Velile; Nevondo, Rendani (Mousaion: South African Journal of Information Studies, 2025)
This study evaluated the effectiveness of strategies employed in organising electronic information resources in academic libraries in Limpopo Province, South Africa. The objectives were to determine the impact of metadata and cataloguing practices on user experience and accessibility, examine the alignment between organisational strategies and user preferences, and identify gaps and innovative approaches in managing electronic resources. A quantitative approach was adopted, involving 115 postgraduate students from three universities in Limpopo Province. Data were collected through structured surveys focusing on metadata consistency, accessibility, and satisfaction with current organisational practices. The analysis, conducted using descriptive and inferential statistics, revealed that metadata plays a central role in enhancing discoverability, usability, and user experience. Postgraduate students demonstrated a strong preference for electronic formats and rely heavily on specialised databases, grey literature, and scholarly repositories to support advanced research. However, resource constraints, technological limitations, and institutional disparities continue to hinder efficiency in resource organisation. The study recommends improving metadata interoperability, investing in AI-driven resource management tools, and strengthening librarian competencies through continuous professional development in metadata curation, digital troubleshooting, and research support. Enhancing technological infrastructure and aligning library services with postgraduate research needs will significantly improve resource accessibility, usability, and overall satisfaction.